2020
DOI: 10.1101/2020.03.23.004192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complex naturalistic stimuli are prioritized by attention when maintained in visual working memory

Abstract: Recent studies suggest that a stimulus actively maintained in working memory (WM) automatically captures visual attention when subsequently perceived. However, such a WM guidance effect has been so far observed only for stimuli defined by simple features, such as colour or orientation. Here we investigated whether the effect occurs also for naturalistic stimuli, whose identity is defined by multiple features and relations among them, specifically for faces and houses. The experiment comprised two conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…When WM cues match target items in a search array (Whitehead et al, 2019), the N2pc component is a lateralized event-related potential (ERP) component that has been found to reflect attentional orientation to a relevant target stimulus (Luck & Hillyard, 1994;Whitehead et al, 2019) with typical onset between 180 and 300 ms (Eimer & Kiss, 2007;Woodman & Luck, 2003). Rutkowska et al (2020) found that participants responded faster when the target was memory-matched with the item in WM content, which also evoked the N2pc, indicating that attention was captured by memory-matched items. On the other hand, search performance declined when the memorymatched items were the distractors in a visual search task, indicating that the attention was captured by WM content (Olivers, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…When WM cues match target items in a search array (Whitehead et al, 2019), the N2pc component is a lateralized event-related potential (ERP) component that has been found to reflect attentional orientation to a relevant target stimulus (Luck & Hillyard, 1994;Whitehead et al, 2019) with typical onset between 180 and 300 ms (Eimer & Kiss, 2007;Woodman & Luck, 2003). Rutkowska et al (2020) found that participants responded faster when the target was memory-matched with the item in WM content, which also evoked the N2pc, indicating that attention was captured by memory-matched items. On the other hand, search performance declined when the memorymatched items were the distractors in a visual search task, indicating that the attention was captured by WM content (Olivers, 2009).…”
Section: Introductionmentioning
confidence: 96%